EFEKTIVITAS MEDIA PEMBELAJARAN ADOBE FLASH TERHADAP KETERAMPILAN MENYANYIKAN LAGU DAERAH PADA KELAS III SD - Pratik Hari Yuwono; Yudha Febrianta (Jurnal Riset Pendidikan Dasar (JRPD), 2020)
Abstract. Multimedia-based learning in elementary schools created in applications to help teachers in art teaching and senior evaluations conducted in learning to make it more interesting. The purpose of this study was to study the effect of adobe flash learning media on the singing skills of folk songs in class III at Muhammadiyah University, Purwokerto. The research subjects used class III students with a total of 24 students. Research methods using experimental research methods. Data analysis using normality test, homogeneity test and hypothesis test. The results of the data analysis and discussion of the results of the study can be concluded about the Adobe Flash learning media on the singing skills of folk songs in class III at Muhammadiyah University, Purwokerto. The results of the first hypothesis test manually, namely tcount> ttable or 2.750> 2.017.